DISEMINASI TEKNOLOGI PENGEMASAN UNTUK MENINGKATKAN DAYA SAING PRODUK OLAHAN PANGAN PADA “KWT SRI TANJUNG”, SUKOSARI, KASEMBON, MALANG - Suprayogi Suprayogi; Nimas Mayang Sabrina; Muhammad Syamsul Hadi; Izzati Ardhan Firdausyi; Isnan Nurdiansyah; Khosid Mahendra Ismail; Ferdyandika Putra Aprilia One; Hikmat Avisenna; Muhamad Toha (Universitas Trisakti, 2021)
Sukosari Village is one of the villages in Kasembon District which has great potential in agriculture. In Sukosari Village, there is a Kelompok Wanita Tani (KWT) called KWT “Sri Tanjung” which has been producing food processing and agricultural handicrafts. Processed food products that have been produced and marketed are corn, cassava, and gadung chips, and packaged drinks called